(untitled) (Modern education and development, 2025)
Teaching food vocabulary to young learners can be both effective and enjoyable through interactive activities. This study explores various interactive methods, such as games, role-playing, storytelling, songs, and hands-on activities, to enhance vocabulary retention and engagement. Young learners benefit from multisensory experiences that make learning more meaningful and memorable. The study highlights how interactive approaches, including real-life simulations like grocery shopping or cooking activities, foster active participation and deeper understanding. Additionally, digital tools and multimedia resources can further support vocabulary acquisition. The findings suggest that integrating interactive activities into language learning improves motivation, comprehension, and long-term retention of food-related vocabulary in young learners.